Plate II: Embryo development of a turtle and chick - Haeckel, Ernst (Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, 1872)
This particular plate illustrates the development of turtle (Schildkröte) and chick (Huhn) embryos. Haeckel's controversial embryo drawings were proven to be incorrect representations of embryos, both in scale and exaggeration. This plate can be found in Ernst Haeckel's Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, or The History of Creation: Or the Development of the Earth and Its Inhabitants by the Action of Natural Causes.
Keywords: Evolution; Heredity; Chickens--Embryos; Turtles; Embryos